Rancang Bangun Alat Pendeteksi Kelayakan Air Menggunakan Sensor PH - Fitri Ariska; Irawan Hadi; Lindawati Lindawati (STIKOM Tunas Bangsa Pematangsiantar, 2019)
One parameter of air quality is the level of turbidity and acidity. For most people, air quality is considered insignificant because it is inappropriate for aesthetics. Good water to be issued according to regulations issued by the government through the Minister of Health of the Republic of Indonesia has a pH value of 6.5 - 8.5 and the maximum turbidity level is 5 NTU (Nephelometric Turbidity Unit). Therefore the author makes a measuring device for acidity in water to facilitate the use of water that will be used by the community. Processing the measurement results is carried out by a pH sensor which will be processed by the Arduino Uno Microcontroller and produced with output via LCD (Liquid Crystal Display). In this test, the author uses several air samples that have been determined by the government, namely pH 4, pH 7 and pH 10. And from several other samples using water that is reasonably suitable for consumption with a pH level of 6.5 and above and can be used as Neutral.